Case Report: Chronic Kidney Failure in Local Dog - Witoko, Maria Clafita; Suartha, I Nyoman; Widyastuti, Sri Kayati (Journal of Veterinary and Animal Sciences; Vol 5 No 2 (2022), 2022)
Chronic kidney failure is defined as a progressive kidney disease that has been going on for several months to years, whereas kidney tissues have lost their function irreversibly. The disease affects dogs of all ages but is more common in older dogs. A Female local dog-weighed 9 kg was examined with complaints of seizures, lethargy, drinking much water, and lost appetite for the past 2 weeks. Clinical examination showed abnormalities in circulation, respiration, and pale mucosal membrane. Complete blood check and biochemistry check then carried out with result showing anemia and significant elevation on BUN (>112 mg/dL) and creatinine (11.2 mg/dL). An ultrasonography examination was about to be carried out but the animal seized again and decided to be carried out when the dog was more stable. With a history of urine incontinence and polydipsia, along with the clinical signs, CBC, and biochemistry blood test, the animal was diagnosed with chronic kidney failure. Diazepam (IV: 0,5 mg/kg BW) and intravenous fluid therapy with RL of 2280 mL/day. After 38 hours of treatment, the dog experienced another seizure and died.